(untitled) (Menara Perkebunan, 2019)
Silica (Si) in the form of soluble silicic acid [H4SiO4] was an element that makes plants more resistant to drought stress through biochemical or molecular processes and contributing to growth stimulation under biotic and abiotic stress conditions. The objective of this study was to determine the response of oil palm seedlings to drought stress by the bio-Si application. The experiment was arranged in complete random design (CRD) with ten replicates. Bio-Si was developed in solid and liquid forms with a dissolved Si content at least 10% (w/v). The eight combinations of solid bio-Si application per seedling were: (i) blank (without fertilizers), (ii) 5 g NPK 15-15-15, (iii) 5 g NPK 15-15-15 + 109cfu of Si-solubilizing microbes (SSM), (iv-viii) 5 g NPK 15-15-15 + 2.5; 5.0; 7.5; 10 g bio-Si; and 5 g Na2SiO3. On the other hand, liquid bio-Si application per seedling were: (i) blank (without fertilizers), (ii) 5 g NPK 15-15-15, (iii) 5 g NPK 15-15-15 + 109cfu of SSM, (iv-viii) 5 g NPK 15-15-15 + 25 mL; 50 mL; 75 mL; 100 mL bio-Si; and 50 mL Na2SiO3. Drought stress tolerance was analyzed by using proline concentration, nitrate reductase activity (NRA), chlorophyll content, and stomatal closure in the leave of oil palm seedlings. Based on the physiological response, this research indicates that bio-Si application could induce seedling tolerance to drought stress. The bio-Si treatments gave a positive response of proline concentration, nitrate reductase activity (NRA), chlorophyll content, and stomatal closure. The doses of 5 g NPK 15-15-15 + 7.5 g solid bio-Si and 5 g NPK 15-15-15 + 75 mL liquid bio-Si per seedling were a recommended to increase oil palm seedlings tolerance to drought stress. [Key words: bio-Si, chlorophyll, nitrate reductase activity, Si-solubilizing microbes]. Abstrak Silika (Si) dalam bentuk terlarut asam silikat [H4SiO4]merupakan unsur yang dapat menyebabkan tanaman lebih tahan terhadap cekaman kekeringan melalui proses biokimia atau molekuler dan menstimulasi pertumbuhan dalam kondisi cekaman biotik dan abiotik. Tujuan dari penelitian ini adalah mengetahui respons fisiologi bibit kelapa sawit yang diberi bio-Si terhadap cekaman kekeringan. Penelitian didesain dengan rancangan acak lengkap (RAL) dan sepuluh ulangan. Bio-Si dikembangkan dalam bentuk padat dan cair dengan kadar Si terlarut minimal 10 % (b/v). Delapan aplikasi bio-Si padat per bibit adalah: (i) blanko (tanpa pupuk), (ii) 5 g NPK 15-15-15, (iii) 5 g NPK 15-15-15 + 109cfu mikrob pelarut silika, (iv-viii) 5 g NPK 15-15-15 + 2,5 g; 5,0 g; 7,5 g; 10 g bio-Si, dan 5 g Na2SiO3. Sementara untuk aplikasi bio-Si cair per bibit adalah: (i) blanko (tanpa pupuk), (ii) 5 g NPK 15-15-15, (iii) 5 g NPK 15-15-15 + 109cfu mikroorganisme pelarut silika (MPS), (iv-viii) 5 g NPK 15-15-15 + 25 ml; 50 ml; 75 ml; dan 100 mLbio-Si, dan 50 ml Na2SiO3. Pengamatan yang dilakukan meliputi analisis prolin, aktivitas nitrat reduktase (ANR), kandungan klorofil, serta morfologi stomata pada daun bibit kelapa sawit. Berdasarkan data fisiologi yang diperoleh dari kegiatan penelitian ini, aplikasi bio-Si dapat meningkatkan ketahanan bibit kelapa sawit terhadap cekaman kekeringan. Perlakuan bio-Si memberikan respon positif terhadap konsentrasi prolin,aktivitas nitrat reduktase (ANR), kandungan klorofil, serta morfologi stomata.Dosis 5 g NPK 15-15-15 + 7,5 g bio-Si padat dan 5 g NPK 15-15-15 + 75 mLbio-Si cair dapat direkomendasikan untuk meningkatkan ketahanan bibit kelapa sawit terhadap cekaman kekeringan. [Kata kunci: bio-Si, klorofil, aktivitas nitrat reduktase, mikroorganisme pelarut silika].